Effect of Carbon Black on the High and Low Temperature Properties of Bitumen - Geckil, Tacettin; Ahmedzade, Perviz; Alatas, Taner (Springer, 2018)
In the present study, the effect of carbon black (CB) as an additive on resistance of bitumen to delay or prevent rutting and low temperature cracking was investigated. For this purpose, different amounts of CB (0, 5, 10, and 15 wt%) were added into bitumen with PG 58-28. Conventional tests (penetration, softening point, Fraass breaking point, ductility, and kinematic viscosity) and Superpave binder tests (rotational viscosity, dynamic shear rheometer, and bending beam rheometer test) were carried out to determine the physical and rheological properties of pure and modified bitumens. In addition, high and low temperature performance grades of pure and modified bitumens were identified according to Superpave binder specification. The results indicated that the addition of CB increased the stiffness and resistance of bitumen to rutting at high temperatures and resistance to thermal cracking at low temperatures of bitumen. Finally, the bitumen becomes more elastic and less susceptible to temperature changes.
Keywords: Carbon black; Bitumen; Aging; Rutting resistance; Performance grade